Study results of rheological and baking parameters of dough from wholemeal bioactivated grain of hulless oats mixed with wheat flour - E. N. Shabolkina; S. N. Shevchenko; N. V. Anisimkina (Зерновое хозяйство России)
In order to improve the biological value of bakery products and consumer properties of new products, there are used the technological additives and functional ingredients, which include bioactivated hulless oats. The purpose of the current work was to estimate the physical, rheological, baking parameters of the dough mixtures obtained by mixing oat flour (wholemeal flour from bioactivated grain) with high-quality premium wheat flour according to the farinographic results and baking analysis. There has been experimentally established that the indicators characterizing the behavior of the dough varied depending on the type of ingredients (wholemeal grain before and after bioactivation) and the proportion of oat processing products (10, 20 %) in the composite mixtures. Dough resistance has decreased on 3.0–7.0 min to wheat flour, valorigraphic estimation at 19–40 u.v. and dough dilution increases significant on 60–160 u.f. The physical properties of the dough when used in mixtures of bioactivated grains slightly have deteriorated compared to non-bioactivated grains: dough resistance and valorigraphic estimation reduced on 0.5–1.0 min and 1–7 u.v., respectively, except for the dough dilution, which improved on 22.0–29.0 %. These processes can be explained by the very high amylolytic activity of the grain after germination. During the trials, there was found an advantage in the general baking assessment in the options using bioactivated oat grain, even though the farinograph recorded a slight deterioration in the physical parameters of the dough. Volume yield was 425–625 cm3 (420–563 cm3 with non-bioactivated grain) and a baking assessment of 2.6–4.4 points versus 2.7–4.3 points. Volume yield increase and baking quality improvement in this case can be explained by the effect of the compensation ability of the mixing strength of wheat. The studied hulless oat varieties ‘Baget’ and ‘Bekas’ in comparison with the chaffy variety ‘Konkur’ in mixtures have shown the best values characterizing the physical properties of the dough and baking quality. They possess better advantage in dough resistance on 1.0–3.0 min., dough dilution on 10–40 u.f. and valorigraphic estimation on 4–17 u.v. They produced 625 cm3 of maximum volume yield, their baking assessment was 4.4 and the tendency remains the same after bioactivation of oat grain.